2014
DOI: 10.1016/j.socscimed.2014.01.032
|View full text |Cite
|
Sign up to set email alerts
|

What factors influence the use of contracts in the context of NHS dental practice? A systematic review of theory and logic model

Abstract: UK NHS contracts mediate the relationship between dental and medical practitioners as independent contractors, and the state which reimburses them for their services to patients. There have been successive revisions of dental and medical contracts since the 1990s alongside a change in the levels of professional dominance and accountability. Unintended consequences of the 2006 dental contract have led to plans for further reform. We set out to identify the factors which facilitate and hinder the use of contract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 26 publications
(37 reference statements)
0
20
0
1
Order By: Relevance
“…It is rare for systematic reviews of theory to assess their quality; this is exemplified by those reviews reported by Campbell et al, 146 Harris et al 147 and Kreiger. 148 Our quality criteria were informed by previous work by Michie et al 64 and Bonell et al, 131 and were accompanied by guidance which was applied by two researchers who then met to discuss their scores.…”
Section: Assessing the Quality Of Theory Reportsmentioning
confidence: 99%
“…It is rare for systematic reviews of theory to assess their quality; this is exemplified by those reviews reported by Campbell et al, 146 Harris et al 147 and Kreiger. 148 Our quality criteria were informed by previous work by Michie et al 64 and Bonell et al, 131 and were accompanied by guidance which was applied by two researchers who then met to discuss their scores.…”
Section: Assessing the Quality Of Theory Reportsmentioning
confidence: 99%
“…85,86 Revenue was a key factor in these data. Dentists could see how the new contract carried the potential for greater value for money and the reduction of unnecessary treatment.…”
Section: Stakeholder Perspectives Of the Blended/incentive-driven Sermentioning
confidence: 90%
“…Initially, contracts were centrally determined and relatively undemanding in terms of performance monitoring. 85 However, since the 1990s, contracts have evolved. The PDS pilots (1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006) 148 encompassed a wide variety of configurations, but concerns were expressed about how they met local needs for service provision, the absence of measures of success or appropriate goals for commissioning and missed opportunities to harness skill mix.…”
Section: Introductionmentioning
confidence: 99%
“…2006. április 1-jétől az elszámo-lási rendszer megváltozott. A korábbi, elsősorban beavatkozásonkénti elszámolást egy kezelésalapú rendszer váltotta fel (UDA rendszer, vagyis Units of Dental Activity) [25].…”
Section: Egyesült Királyságunclassified